Pembelajaran NHT Menggunakan Alat Peraga untuk Meningkatkan Hasil Belajar Siswa di Ma Baitulmal Pancasila - Fitri , Sulistika Rahayu; S, Haratua Tiur Maria; H, Muhammad Musa Syarif (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The objective of this research is to assess the impact of employing the Numbered Head Together (NHT) learning method with instructional aids on students' comprehension of Hooke's Law at MA Baitulmal Pancasila Nanga Pinoh, both before and after implementation. This study adopts a one-group pretest and posttest design, utilizing essay-based research instruments. Data collection involves measurement tests, aligning with the experimental nature of the research to evaluate the efficacy of NHT learning with instructional aids in enhancing student performance on Hooke's Law. The assessment tools consist of pretest and posttest assessments, each comprising five essay questions. Data analysis focuses on identifying the number and percentage of students who answered questions incorrectly. The study concentrates on the sub-topics of Hooke's Law in series and parallel series, employing the NHT cooperative learning method. Results indicate a pretest average score of 31.88 in the low category, improving to a posttest average of 61.76 in the medium category. This discerns that utilizing the NHT cooperative learning approach with instructional aids enhances student learning outcomes concerning Hooke's Law at MA Baitulmal Pancasila Nanga Pinoh.